Kegiatan Seleksi Bahan Pustaka di Perpustakaan Perguruan Tinggi - Rosiana Nurwa Indah; Miftahunnisa' Igiriza (Fakultas Ilmu Komunikasi Universitas Islam Nusantara, 2021)
This study aims to determine the activities of selection of library materials in university libraries. The research location is in the Library of the Faculty of Arts and Letters (FISS) Pasundan University. The research method used is through qualitative methods. Collecting data through observation, interviews and documentation. The informants in this study were the head of the library and two librarians. The results showed that in selecting library materials, the Faculty of Arts and Letters (FISS) Pasundan University had identified the characteristics of the use of the library. In addition, it has paid attention to the criteria and stages of implementing the selection of library materials which are usually applied to university libraries. The obstacles faced in the selection process were the difficulty of obtaining a selector team from librarians, curriculum changes, limited selection tools often used by librarians, the large number of collections with art subjects that had to be given from abroad which tended to be expensive, and the Covid-19 pandemic which create a library must provide electronic collections. In dealing with the various obstacles above, the library involves lecturers, experts and deans as a selector team. In addition, it cooperates with various other libraries and informs its users of various electronic reference sources that are easily accessible and free of charge. Thus, the Library of the Faculty of Arts and Letters (FISS) of Pasundan University can still provide collection materials that are in accordance with the needs of its users that support the Tri Dharma of Higher Education can be achieved.Keyword: selection of library materials, college librariesABSTRAKPenelitian ini bertujuan untuk mengetahui kegiatan seleksi bahan pustaka di perpustakaan perguruan tinggi. Adapun lokasi penelitian di Pepustakaan Fakultas Ilmu Seni dan Sastra (FISS) Universitas Pasundan. Metode penelitian yang digunakan melalui metode kualitatif. Pengumpulan data melalui observasi, wawancara dan dokumentasi. Informan dalam penelitian ini adalah Kepala Perpustakaan dan dua orang pustakawan. Hasil penelitian menunjukkan bahwa dalam melakukan seleksi bahan pustaka Perpustakaan Fakultas Ilmu Seni dan Sastra (FISS) Universitas Pasundan sudah melakukan identifikasi mengenai karakteristik penggunaan perpustakaannya. Selain itu, sudah memperhatikan kriteria dan tahapan pelaksanaan seleksi bahan perpustakaan yang biasanya diterapkan pada perpustakaan perguruan tinggi. Adapun hambatan yang dihadapi dalam proses seleksi adalah sulitnya memperoleh tim selektor dari pustakawan, adanya perubahan kurikulum, terbatasnya alat bantu seleksi yang sering digunakan oleh pustakawan, banyaknya koleksi dengan subjek seni yang harus diberi dari luar negeri yang cenderung mahal dan adanya Pandemi Covid-19 yang membuat perpustakaan harus menyediakan koleksi elektronik. Dalam menghadapi berbagai hambatan di atas maka perpustakaan melibatkan dosen, kepakaran dan dekan sebagai tim selektor. Selain itu, melakukan kerjasama dengan berbagai perpustakaan lain serta menginformasikan berbagai sumber refrensi elektronik yang mudah diakses dan gratis kepada pada penggunanya. Dengan demikian, Perpustakaan Fakultas Ilmu Seni dan Sastra (FISS) Universitas Pasundan tetap dapat menyediakan bahan koleksi yang sesuai dengan kebutuhan penggunannya yang mendukung Tri Dharma Perguruan Tinggi dapat tecapai.